Double-network interpenetrating shape memory solid electrolyte and preparation method thereof
Through the preparation method of shape memory solid electrolyte with dual network interpenetration, the problem of single function in the prior art is solved, and the combination of high ionic conductivity and shape memory performance is achieved. It is suitable for multifunctional intelligent materials in the aerospace field.
Patent Information
- Application Number
- CN202411254186.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The existing all-solid-state electrolyte has a single function, making it difficult to have both electrolyte functions and shape memory performance, and cannot meet the demand for multifunctional intelligent materials in the aerospace field.
Using a dual network interpenetrating shape memory solid electrolyte preparation method, the first functional monomer, polymer electrolyte monomer and macromolecular initiator are mixed and reacted to form an ionic conductive polymer network colloid, and intersected with the second functional monomer. The coupling agent is cross-linked with the lithium electrolyte to form a shape memory solid electrolyte with dual network interpenetration.
It achieves a combination of high ionic conductivity, mechanical strength and shape memory performance, effectively inhibits the growth of lithium dendrites, and is suitable for multifunctional intelligent materials in the aerospace field.
Smart Images

Figure CN119285844A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer electrolytes, and in particular to a double-network interpenetrating shape memory solid electrolyte and a preparation method thereof. Background Art
[0002] With the development of new energy vehicles and other fields, higher requirements are placed on lithium-ion batteries, especially in terms of high power, high energy density and high safety performance. Currently, commercial lithium-ion batteries generally use flammable, explosive and volatile organic electrolytes, which pose extremely high safety risks. In addition, the growth of lithium dendrites in liquid electrolytes also hinders the practical application of lithium metal anodes in rechargeable batteries. In order to meet these challenges, the use of all-solid-state electrolytes to replace electrolytes containing organic liquids is an important way to solve battery safety problems.
[0003] At present, the all-solid-state electrolytes that have been widely studied mainly include polymer-based electrolytes, inorganic oxide electrolytes, sulfide electrolytes, and organic-inorganic composite electrolytes. However, the functions of the above-mentioned all-solid-state electrolytes are relatively single, and it is difficult to have both electrolyte functions and shape memory properties, thus failing to meet the needs of the aerospace field for multifunctional smart materials.
[0004] Therefore, based on the above problems, there is an urgent need to provide a double-network interpenetrating shape memory solid electrolyte and a preparation method thereof. Summary of the invention
[0005] The embodiment of the present invention provides a double-network interpenetrating shape memory solid electrolyte and a preparation method thereof, which can solve the problem that the solid electrolyte in the prior art has a single function and is difficult to meet the demand for multifunctional intelligent materials in the aerospace field.
[0006] In a first aspect, the present invention provides a method for preparing a double network interpenetrating shape memory solid electrolyte, the preparation method comprising the following steps:
[0007] (1) adding a first functional monomer, a polymer electrolyte monomer and a macromolecular initiator into a first organic solvent and mixing them for reaction to obtain an ion conductive polymer network colloid; wherein the first functional monomer comprises an epoxy group and a carbon-carbon double bond;
[0008] (2) adding the ion conductive polymer network colloid, the second functional monomer, the crosslinking agent and the electrolyte lithium salt into a second organic solvent for mixing and crosslinking to obtain the double network interpenetrating shape memory solid electrolyte; wherein the second functional monomer contains an epoxy group.
[0009] Preferably, in step (1), the first functional monomer is glycidyl methacrylate; the polymer electrolyte monomer is poly(ethylene glycol) methyl ether methacrylate; the macromolecular initiator is tetrahydroxymethylpropane tris(2-bromoisobutyrate) or trihydroxymethylpropane tris(2-bromoisobutyrate); and the first organic solvent is toluene or ethylbenzene.
[0010] Preferably, the second functional monomer is bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, epoxy novolac resin or bisphenol S diglycidyl ether; the crosslinking agent is polyetheramine, polyetherdiamine or polyethertriamine; the electrolyte lithium salt is lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonate imide, lithium difluorooxalatoborate or lithium dioxalatoborate; and the second organic solvent is acetonitrile solution.
[0011] Preferably, in step (1), during the preparation of the ion conductive polymer network colloid, the content of the first functional monomer is 1-10%, the content of the polymer electrolyte monomer is 60-90%, the content of the macromolecular initiator is 0.1-2%, and the content of the first organic solvent is 2-15%, measured in weight percentage.
[0012] Preferably, in step (2), the mass ratio of the ion-conductive polymer network colloid to the second functional monomer is 1:(1-3); the content of the cross-linking agent is 20-25% of the total amount of the ion-conductive polymer network colloid and the second functional monomer;
[0013] In the preparation of the double-network interpenetrating shape memory solid electrolyte, the content of the electrolyte lithium salt is 0.5-1% and the content of the second organic solvent is 10-20% by weight.
[0014] Preferably, in step (2), before the cross-linking reaction is carried out, a step of adding a catalytic monomer to the reaction system is also included; wherein the catalytic monomer includes 1,1,4,7,10,10-hexamethyltriethylenetetramine and copper bromide.
[0015] Preferably, the content of the catalytic monomer is 0.2-4% by weight.
[0016] Preferably, the reaction temperature is 70-80°C and the reaction time is 2-6h.
[0017] Preferably, in step (2), the cross-linking temperature is 15-25° C. and the time is 10-12 h.
[0018] In a second aspect, the present invention further provides a double-network interpenetrating shape memory solid electrolyte, which is prepared by the preparation method described in any one of the first aspects above.
[0019] In a third aspect, the present invention also provides an application of a double-network interpenetrating shape memory solid electrolyte prepared by any preparation method described in the first aspect or a double-network interpenetrating shape memory solid electrolyte described in the second aspect in a lithium battery.
[0020] Compared with the prior art, the present invention has at least the following beneficial effects:
[0021] In the present invention, firstly, the first functional monomer containing epoxy groups and carbon-carbon double bonds and the polymer electrolyte monomer react under the action of a macromolecular initiator to form an ion-conducting polymer network colloid with ion conductivity and high strength performance, and then based on the network colloid, the second functional monomer containing epoxy groups and the electrolyte lithium salt are added to further react under the action of a crosslinking agent, and the second functional monomer can first react with the crosslinking agent to form a polymer network with shape memory performance, and then the polymer network can further interpenetrate and crosslink with the ion-conducting polymer network to form a double network interpenetrating shape memory solid electrolyte. In this way, the solid polymer electrolyte with a double network interpenetrating structure obtained in the present invention not only exhibits high ion conductivity and high strength, but also allows uniform current distribution to effectively inhibit the growth of lithium dendrites; at the same time, the solid polymer electrolyte also has the function of a shape memory smart carrier, has good compatibility with the positive electrode, and can meet the needs of the aerospace field for multifunctional smart materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 It is a schematic structural diagram of a double-network interpenetrating shape memory solid electrolyte provided by one embodiment of the present invention; the black network is a polymer network structure with shape memory function, and the gray dotted network is an ion conductive polymer network structure. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] The present invention provides a method for preparing a double-network interpenetrating shape memory solid electrolyte, the preparation method comprising the following steps:
[0026] (1) adding a first functional monomer, a polymer electrolyte monomer and a macromolecular initiator into a first organic solvent and mixing them for reaction to obtain an ion conductive polymer network colloid; wherein the first functional monomer comprises an epoxy group and a carbon-carbon double bond;
[0027] (2) adding the ion conductive polymer network colloid, the second functional monomer, the crosslinking agent and the electrolyte lithium salt into a second organic solvent for mixing and crosslinking to obtain the double network interpenetrating shape memory solid electrolyte; wherein the second functional monomer contains an epoxy group.
[0028] In the embodiment of the present invention, the first functional monomer containing epoxy groups and carbon-carbon double bonds and the polymer electrolyte monomer are first reacted under the action of a macromolecular initiator to form an ion-conducting polymer network colloid with ion conductivity and high strength performance, and then the network colloid is further reacted with a second functional monomer containing epoxy groups and an electrolyte lithium salt under the action of a crosslinking agent, and the second functional monomer can first react with the crosslinking agent to form a polymer network with shape memory performance, and then the polymer network can further interpenetrate and crosslink with the ion-conducting polymer network to form a double network interpenetrating shape memory solid electrolyte. In this way, the solid polymer electrolyte with a double network interpenetrating structure obtained in the present invention not only exhibits high ion conductivity and high strength, but also allows uniform current distribution to effectively inhibit the growth of lithium dendrites; at the same time, the solid polymer electrolyte also has a shape memory smart carrier function, has good compatibility with the positive electrode, and can meet the needs of the aerospace field for multifunctional smart materials.
[0029] According to some preferred embodiments, in step (1), the first functional monomer is glycidyl methacrylate; the polymer electrolyte monomer is poly(ethylene glycol) methyl ether methacrylate; the macromolecular initiator is tetrahydroxymethylpropane tris(2-bromoisobutyrate) or trihydroxymethylpropane tris(2-bromoisobutyrate); and the first organic solvent is toluene or ethylbenzene.
[0030] In an embodiment of the present invention, by preferably selecting glycidyl methacrylate as the first functional monomer, which contains both an epoxy group and a carbon-carbon double bond and has a relatively short molecular chain, and reacting it with a macromolecular initiator and a polymer electrolyte monomer, it is not only beneficial to ensure that the formed polymer network has good mechanical properties, but also beneficial to the subsequent further reaction with other monomers to form a double network interpenetrating structure; at the same time, the use of the above-mentioned type of polymer electrolyte monomer can not only give the polymer network good ionic conductivity, but also after further cross-linking it with the second functional monomer and the cross-linking agent, it will not have an adverse effect on the shape memory properties of the solid electrolyte, which is beneficial to ensure that the solid electrolyte has both good shape memory properties and ionic conductivity properties.
[0031] In the process of preparing the ion-conductive polymer network colloid, in order to ensure good reaction efficiency, the first functional monomer, the polymer electrolyte monomer and the macromolecular initiator are added to the first organic solvent under a nitrogen atmosphere, and the solution is degassed three times by a freeze pump thawing cycle, and then placed in an oil bath at 70-80° C. for reaction, thereby preparing the ion-conductive polymer network colloid, whose structural formula is as follows:
[0032] Among them, the wavy line does not represent any group, but only indicates the position where the carbon-carbon double bond is opened and combined with the Br-containing alkyl group. R1 is any alkyl group. The specific values of x and y are not particularly limited and can be adjusted by adjusting the ratio of the first functional monomer and the polymer electrolyte monomer.
[0033] At the same time, in order to remove impurities in the ion conductive polymer network colloid, after the reaction is completed, the reaction solution is diluted with tetrahydrofuran, placed in a neutral alumina column for filtration to remove copper salts, and the filtered product is precipitated twice with excess ether. After filtering and vacuum drying in turn, a high-purity ion conductive polymer network colloid can be obtained.
[0034] It should be noted that, in order to ensure that the solid electrolyte has a suitable cross-linking density, in the embodiment of the present invention, the structural formula of the polymer electrolyte monomer (poly (ethylene glycol) methyl ether methacrylate) is as follows:
[0035] n is a repeating unit, and its value ranges from 2 to 500.
[0036] According to some preferred embodiments, the second functional monomer is bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, epoxy novolac resin or bisphenol S diglycidyl ether; the cross-linking agent is polyether amine, polyether diamine or polyether triamine; the electrolyte lithium salt is lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonate imide, lithium difluorooxalatoborate or lithium dioxalatoborate; and the second organic solvent is acetonitrile solution.
[0037] In the embodiment of the present invention, when the above-mentioned second functional monomer, cross-linking agent and electrolyte lithium salt are mixed with the ion conductive polymer network colloid for reaction, the second functional monomer can react with the above-mentioned cross-linking agent first, thereby forming a shape memory polymer network with shape memory performance and good strength, and its structural formula is as follows:
[0038] Among them, the wavy lines do not represent any groups, but only indicate the bonding positions containing amino and epoxy groups;
[0039] Afterwards, the shape memory polymer network can further undergo polymerization reaction with the ion conductive polymer network colloid, thereby forming a solid electrolyte with two network structures of shape memory polymer network and ion conductive polymer network interpenetrating and cross-linking (such as Figure 1 This interpenetrating cross-linked solid polymer electrolyte not only exhibits high ionic conductivity, allows uniform current distribution, and thus effectively inhibits lithium dendrite growth, allowing lithium-ion batteries to exhibit excellent cycle stability, but also has excellent mechanical strength, which can improve the safety performance of lithium batteries. At the same time, it also has a shape memory smart carrier function, has good compatibility with the positive electrode, and is easy to process.
[0040] It should be noted that the cross-linking agent in the embodiment of the present invention is preferably a polyetheramine, and the structural formula of the polyetheramine is as follows:
[0041] n is a repeating unit, and its value is 9-34; using the cross-linking agent with the above molecular weight to react with the second functional monomer is beneficial to ensure the good mechanical properties of the solid electrolyte.
[0042] According to some preferred embodiments, in step (1), during the preparation of the ion conductive polymer network colloid, the content of the first functional monomer is 1-10% (for example, 1%, 2%, 3%, 5%, 8% or 10%), the content of the polymer electrolyte monomer is 60-90% (for example, 60%, 70%, 80% or 90%), the content of the macromolecular initiator is 0.1-2% (for example, 0.1%, 0.5%, 1%, 1.5% or 2%), and the content of the first organic solvent is 2-15% (for example, 2%, 5%, 8%, 10%, 12% or 15%).
[0043] In the embodiment of the present invention, when preparing the ion conductive polymer network colloid, by further reasonably controlling the content of each reaction raw material, it is beneficial to prepare an ion conductive polymer network structure with good ion conductivity, good strength and relatively stable structure; at the same time, according to the actual demand for ion conductivity and structural strength, the amount of the first functional monomer and the polymer electrolyte monomer can be adjusted to adjust the values of the x and y values in the ion conductive polymer network structure, thereby adjusting the ion conductivity and structural strength of the network structure. However, if the content of the first functional monomer is too much, it is not conducive to ensuring the good ion conductivity of the polymer network structure. If the content of the polymer electrolyte monomer is too much, the structure of the prepared solid electrolyte is relatively soft, which is not conducive to ensuring good mechanical strength.
[0044] According to some preferred embodiments, in step (2), the mass ratio of the ion conductive polymer network colloid and the second functional monomer is 1:(1-3) (for example, it can be 1:1, 1:2 or 1:3); the content of the cross-linking agent is 20-25% of the total amount of the ion conductive polymer network colloid and the second functional monomer (for example, it can be 20%, 21%, 22%, 23%, 24% or 25%); in the preparation of the double network interpenetrating shape memory solid electrolyte, the content of the electrolyte lithium salt is 0.5-1% (for example, it can be 0.5%, 0.8% or 1%), and the content of the second organic solvent is 10-20% (for example, it can be 10%, 15% or 20%).
[0045] In the embodiment of the present invention, by controlling the contents of the ion conductive network colloid, the second functional monomer and the cross-linking agent, it is beneficial to prepare a solid electrolyte having good shape memory performance, ion conductive performance and good mechanical strength; if the content of the ion conductive polymer network colloid is too little, the conductivity of the solid electrolyte will decrease, but if the content of the ion conductive polymer network colloid is too much, the ratio of the ion conductive polymer network and the shape memory polymer network will be unbalanced, which is not conducive to ensuring the good shape memory performance of the solid electrolyte.
[0046] It should be noted that, in the embodiment of the present invention, in order to ensure good ionic conductivity of the solid electrolyte, a lithium salt with a concentration of 1 mol / L is used to react with the above reactants.
[0047] According to some preferred embodiments, in step (1), before the cross-linking reaction is carried out, a step of adding a catalytic monomer to the reaction system is further included; wherein the catalytic monomer includes 1,1,4,7,10,10-hexamethyltriethylenetetramine and copper bromide. In terms of weight percentage, the content of the catalytic monomer is 0.2-4% (for example, it can be 0.2%, 0.5%, 0.8%, 1%, 2%, 3% or 4%).
[0048] In the embodiment of the present invention, by adding a proper amount of the above-mentioned catalytic monomers to the reaction system, the reaction is promoted and the reaction efficiency is increased; the mass ratio of the two catalytic monomers is preferably 1:1.
[0049] According to some preferred embodiments, in step (1), the reaction temperature is 70-80°C (for example, 70°C, 72°C, 75°C, 78°C or 80°C), and the time is 2-6h (for example, 2h, 3h, 5h or 6h); in step (2), the cross-linking temperature is 15-25°C (for example, 15°C, 18°C, 20°C, 22°C or 25°C), and the time is 10-12h (for example, 10h, 11h or 12h).
[0050] In an embodiment of the present invention, after the reaction is completed, the reacted liquid can be poured into a mold coated with polytetrafluoroethylene, and further heated at 80°C for 12-48 hours to ensure sufficient reaction, and then demolded and dried at 70-90°C for 12-48 hours to obtain the above-mentioned double-network interpenetrating shape memory solid electrolyte.
[0051] An embodiment of the present invention further provides a double-network interpenetrating shape memory solid electrolyte, which is prepared by any of the preparation methods described above.
[0052] An embodiment of the present invention also provides an application of the double-network interpenetrating shape memory solid electrolyte described in any one of the above items in a lithium battery.
[0053] The solid electrolyte prepared in the embodiment of the present invention has good ionic conductivity and mechanical strength, and has good shape memory performance, and can undergo shape change through external stimulation (such as thermal stimulation, etc.). The glass transition temperature of the solid electrolyte material in the embodiment of the present invention is about 60°C, and it has great application potential in smart materials and devices. When applied to lithium batteries, it can solve the problems of poor safety and low energy density of existing solid-state batteries.
[0054] In order to more clearly illustrate the technical solution and advantages of the present invention, a double-network interpenetrating shape memory solid electrolyte and a preparation method thereof are described in detail through several embodiments below.
[0055] Embodiment 1:
[0056] (1) adding 5 wt % of the first functional monomer (glycidyl methacrylate), 75 wt % of the polymer electrolyte monomer (poly(ethylene glycol) methyl ether methacrylate), 0.5 wt % of the macroinitiator (tetrahydroxymethylpropane tris(2-bromoisobutyrate)), and 1 wt % of the catalytic monomer (1,1,4,7,10,10-hexamethyltriethylenetetramine and copper bromide in a mass ratio of 1:1) into a Schlenk flask filled with 8 wt % of anhydrous toluene, and stirring and mixing;
[0057] The solution was degassed three times using a freeze-pump-thaw cycle, and the flask was immersed in an oil bath preheated to 75°C. After reacting for 4 hours, the flask was quenched in liquid nitrogen. The reacted solution was diluted with 300 mL of tetrahydrofuran, passed through a neutral alumina column to remove copper salts, and precipitated twice with 2 L of ether. After filtering and vacuum drying at 45°C, an ion-conductive polymer network colloid was obtained.
[0058] (2) An ion conductive polymer network colloid and a second functional monomer (bisphenol A diglycidyl ether) are mixed in a mass ratio of 1:1, and a cross-linking agent (polyether amine), an electrolyte lithium salt (lithium bistrifluoromethanesulfonyl imide) and 10 wt % of a second organic solvent (acetonitrile solution) are added, and the mixture is stirred and reacted at 25° C. for 12 h to obtain a reaction precursor solution, and the reaction precursor solution is poured into a mold coated with polytetrafluoroethylene, and the temperature is raised to 80° C. and the reaction is continued for 4 h. After cooling and demolding, the mixture is further vacuum dried at 80° C. for 24 h to obtain a double network interpenetrating shape memory solid electrolyte; wherein the amount of the cross-linking agent added is 20% of the total amount of the ion conductive polymer network colloid and the second functional monomer, and the amount of the electrolyte lithium salt added is 1 wt %.
[0059] Embodiment 2:
[0060] Example 2 is basically the same as Example 1, except that: in step (1), the content of the first functional monomer (glycidyl methacrylate) is 10wt%, and the content of the polymer electrolyte monomer (poly(ethylene glycol) methyl ether methacrylate) is 60wt%; and in step (2), the mass ratio of the ion conductive polymer network colloid to the second functional monomer is 1:2.
[0061] Embodiment 3:
[0062] Example 3 is basically the same as Example 1, except that: in step (1), the content of the first functional monomer (glycidyl methacrylate) is 8wt%, and the content of the polymer electrolyte monomer (poly(ethylene glycol) methyl ether methacrylate) is 70wt%; and in step (2), the mass ratio of the ion conductive polymer network colloid to the second functional monomer is 1:3.
[0063] Embodiment 4:
[0064] Example 4 is substantially the same as Example 1, except that in step (2), the mass ratio of the ion conductive polymer network colloid to the second functional monomer is 1:2.
[0065] Embodiment 5:
[0066] Example 5 is substantially the same as Example 1, except that in step (2), the mass ratio of the ion conductive polymer network colloid to the second functional monomer is 1:3.
[0067] Embodiment 6:
[0068] Example 6 is basically the same as Example 1, except that in step (1), the content of the first functional monomer is 15 wt %.
[0069] Embodiment 7:
[0070] Example 7 is substantially the same as Example 1, except that in step (1), the content of the polymer electrolyte monomer is 95 wt %.
[0071] Embodiment 8:
[0072] Example 8 is substantially the same as Example 1, except that in step (1), the content of the macroinitiator is 5 wt %.
[0073] Embodiment 9:
[0074] Example 9 is substantially the same as Example 1, except that in step (2), the mass ratio of the ion conductive polymer network colloid to the second functional monomer is 1:4.
[0075] Comparative Example 1:
[0076] (1) adding 5 wt % of the first functional monomer (glycidyl methacrylate), 75 wt % of the polymer electrolyte monomer (poly(ethylene glycol) methyl ether methacrylate), 0.5 wt % of the macroinitiator (tetrahydroxymethylpropane tris(2-bromoisobutyrate)), and 1 wt % of the catalytic monomer (1,1,4,7,10,10-hexamethyltriethylenetetramine and copper bromide in a mass ratio of 1:1) into a Schlenk flask filled with 8 wt % of anhydrous toluene, and stirring and mixing;
[0077] The solution was degassed three times using a freeze-pump-thaw cycle, and the flask was immersed in an oil bath preheated to 75°C. After reacting for 4 hours, the flask was quenched in liquid nitrogen. The reacted solution was diluted with 300 mL of tetrahydrofuran, passed through a neutral alumina column to remove copper salts, and precipitated twice with an excess of 2 L of ether. After filtering and vacuum drying at 45°C, an ion-conductive polymer network colloid was obtained.
[0078] (2) adding a crosslinking agent (polyether amine) and an electrolyte lithium salt (lithium bis(trifluoromethanesulfonyl imide)) to the ion conductive polymer network colloid, stirring and mixing at 25°C for 12 hours to obtain a reaction precursor solution, pouring the reaction precursor solution into a mold coated with polytetrafluoroethylene, heating to 80°C and continuing the reaction for 4 hours, cooling and demolding, and further vacuum drying at 80°C for 24 hours to obtain a solid electrolyte; wherein the amount of the crosslinking agent added is 20% of the ion conductive polymer network colloid, and the amount of the electrolyte lithium salt added is 1wt%.
[0079] The solid electrolytes prepared in Examples 1 to 9 and Comparative Example 1 (hereinafter referred to as samples) were subjected to performance tests, and the test results are shown in Table 1;
[0080] Young's modulus test standard: ASTM D638: Standard test method for tensile properties of plastics;
[0081] Specific test method: The tensile specimen is stretched by a universal testing machine (UTM), and the applied stress and generated strain are measured. The Young's modulus is the slope of the linear part of the stress-strain curve.
[0082] Electrochemical window test: Utilize linear sweep voltammetry to test, specifically, place the sample in a battery, usually using a three-electrode system: a working electrode (such as Pt or glassy carbon electrode), a reference electrode (such as Ag / AgCl) and a counter electrode (such as platinum sheet or graphite), gradually increase the potential, starting from a stable state, and record the current; analyze the obvious current rising points in the voltage and current curve, that is, the voltage at which the electrolyte begins to decompose. These points represent the upper and lower limits of the electrochemical window.
[0083] Ionic conductivity test: Test steps: Place the sample to be tested in a two-electrode fixture, usually stainless steel, electroplated platinum or other inert electrodes, use an electrochemical impedance spectroscopy instrument, apply an AC signal ranging from a few Hz to a few MHz, measure and record the phase difference between voltage and current, and obtain the impedance spectrum of the sample (Nyquist diagram). Determine the resistance of the sample through equivalent circuit fitting analysis, and calculate the ionic conductivity based on the thickness and surface area of the sample;
[0084] Shape memory performance test: prepare the above sample into a film, then fix the temporary shape at 10-20°C above Tg (response temperature), fix it at a temperature below Tg (such as room temperature 20-30°C), raise the temperature of the fixed sample to above Tg, and judge the shape memory performance of the sample based on the shape memory recovery rate and fixation rate; judging criteria: higher than 85% (good), higher than 95% (excellent), and lower than 50% does not have shape memory performance.
[0085] Table 1
[0086]
[0087] From Table 1 and Figure 1 It can be seen that, compared with the comparative example, the solid electrolyte prepared in the embodiment of the present invention is formed by interpenetrating and cross-linking a shape memory polymer network and an ion conductive polymer network. The solid electrolyte not only has a high ionic conductivity and can effectively inhibit the growth of lithium dendrites, but also has good mechanical strength and good high voltage resistance. At the same time, it also has good shape memory performance and can undergo shape change through external stimulation, and has great application potential in smart materials and devices.
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a double network interpenetrating shape memory solid electrolyte, characterized in that: The preparation method comprises the following steps: (1) adding a first functional monomer, a polymer electrolyte monomer and a macromolecular initiator into a first organic solvent and mixing them for reaction to obtain an ion conductive polymer network colloid; wherein the first functional monomer comprises an epoxy group and a carbon-carbon double bond; (2) adding the ion conductive polymer network colloid, the second functional monomer, the crosslinking agent and the electrolyte lithium salt into a second organic solvent for mixing and crosslinking to obtain the double network interpenetrating shape memory solid electrolyte; wherein the second functional monomer contains an epoxy group.
2. The preparation method according to claim 1, characterized in that: In step (1), the first functional monomer is glycidyl methacrylate; the polymer electrolyte monomer is poly(ethylene glycol) methyl ether methacrylate; the macromolecular initiator is tetrahydroxymethylpropane tris(2-bromoisobutyrate) or trihydroxymethylpropane tris(2-bromoisobutyrate); and the first organic solvent is toluene or ethylbenzene.
3. The preparation method according to claim 1, characterized in that: The second functional monomer is bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, epoxy phenolic resin or bisphenol S diglycidyl ether; the cross-linking agent is polyether amine, polyether diamine or polyether triamine; the electrolyte lithium salt is lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonate imide, lithium difluorooxalatoborate or lithium dioxalatoborate; and the second organic solvent is acetonitrile solution.
4. The preparation method according to claim 1, characterized in that: In step (1), during the preparation of the ion conductive polymer network colloid, by weight percentage, the content of the first functional monomer is 1-10%, the content of the polymer electrolyte monomer is 60-90%, the content of the macromolecular initiator is 0.1-2%, and the content of the first organic solvent is 2-15%.
5. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the ion-conductive polymer network colloid to the second functional monomer is 1:(1-3); the content of the cross-linking agent is 20-25% of the total amount of the ion-conductive polymer network colloid and the second functional monomer; and / or In the preparation of the double-network interpenetrating shape memory solid electrolyte, the content of the electrolyte lithium salt is 0.5-1% and the content of the second organic solvent is 10-20% by weight.
6. The preparation method according to claim 1, characterized in that: In step (2), before the cross-linking reaction is carried out, a step of adding a catalytic monomer to the reaction system is also included; wherein the catalytic monomer includes 1,1,4,7,10,10-hexamethyltriethylenetetramine and copper bromide.
7. The preparation method according to claim 6, characterized in that: In terms of weight percentage, the content of the catalytic monomer is 0.2-4%.
8. The preparation method according to claim 1, wherein in step (1), the reaction temperature is 70-80°C and the reaction time is 2-6h; and / or In step (2), the cross-linking temperature is 15-25°C and the time is 10-12h.
9. A double network interpenetrating shape memory solid electrolyte, characterized in that: The preparation method is described in any one of claims 1 to 8.
10. Use of the double-network interpenetrating shape memory solid electrolyte prepared by the preparation method according to any one of claims 1 to 8 or the double-network interpenetrating shape memory solid electrolyte according to claim 9 in a lithium battery.
Citation Information
Patent Citations
Single-ion polymer solid electrolyte with semi-interpenetrating network structure and preparation method of single-ion polymer solid electrolyte
CN114865070A
Solid electrolyte precursor solution, solid electrolyte, and preparation method and application of solid electrolyte precursor solution and solid electrolyte
CN115621544A
Solid electrolyte, preparation method and application thereof
CN117855598A
Composite solid electrolyte as well as preparation method and application thereof
CN118173864A
Gel electrolyte and preparation method and application thereof
CN118185072A